THE CATALOGUE OF PHOTOMETRIC, GEOMETRICAL AND ABSOLUTE ELEMENTS OF CONTACT BINARY STARS OF THE EARLY SPECTRAL TYPE - Bondarenko, I. I.; Perevozkina, E. L. (Одеські астрономічні публікації, 2017)
The Catalogue of the early type contact systems is described and its analysis is presented.